Short carbon fiber toughened ternary ceramic matrix composite material and preparation method thereof

Through gas blowing method and reactive hot pressing sintering technology, the problems of uneven dispersion of short carbon fibers and difficulty in sintering densification in ultra-high temperature ceramic matrix composites are solved, achieving high flexural strength and fracture toughness of the material, and reducing the sintering temperature. .

CN119350038AActive Publication Date: 2025-01-24WUZHEN LABORATORY
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411921147.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The prior art is difficult to evenly disperse short carbon fibers in ultra-high temperature ceramic matrix composite materials, resulting in fiber damage and difficulty in sintering and densification.

Method used

The short carbon fibers are added to the ceramic matrix mixed slurry using the gas blowing method, and the short carbon fibers are uniformly dispersed and long-length retained through wet ball milling mixing and reaction hot pressing sintering.

Benefits of technology

The uniform distribution of short carbon fibers in ceramic base composite materials, high -bending strength, fracture toughness, and reducing the sintering temperature, avoiding the impact of the high temperature performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350038A_ABST
    Figure CN119350038A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aerospace material preparation, in particular to a short carbon fiber toughened ternary ultrahigh-temperature ceramic matrix composite material and a preparation method thereof. According to the preparation method provided by the invention, the short carbon fibers are promoted to be uniformly dispersed and the damage is inhibited through a short carbon fiber dispersion mode of blowing away gas, and residual oxides are removed through the reaction of residual carbon and oxides after ball-milling wrapping resin cracking so as to promote densification; and the material is prepared by reactive hot pressing sintering without adding a second-phase sintering aid. The short carbon fiber toughened ternary ultra-high-temperature ceramic matrix composite material prepared by the preparation method disclosed by the invention is low in sintering temperature, uniform in short carbon fiber distribution, relatively long in length, high in bending strength and fracture toughness and good in densification degree.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerospace material preparation, in particular to a short carbon fiber toughened ternary ceramic matrix composite material and a preparation method thereof. Background Art

[0002] Ultrahigh temperature ceramics (such as ZrB2, ZrC, HfB2, HfC, TaB2, TaC, TiB2, TiC, HfN, etc.) have excellent physical and chemical properties, such as high melting point, high hardness, high modulus, good thermal shock resistance and oxidation resistance, which makes them potential candidates for ultrahigh temperature structural applications in the aerospace field. However, due to the strong covalent bonds and low self-diffusion coefficients of ultrahigh temperature ceramics themselves, extremely high temperatures (>2000℃) are often required to achieve densification without the addition of sintering aids. Although the addition of sintering aids (such as Ni, Nb, Mo, MoSi2, ZrSi2, Si3N4, AlN, WC, etc.) can significantly reduce the sintering densification temperature of ultrahigh temperature ceramics and produce a fine-grained microstructure, these sintering aids remain in the ceramic matrix and form a low-melting intermediate phase, which will cause the material to creep at high temperatures and seriously affect the high-temperature properties of the material.

[0003] In addition, although ultra-high temperature ceramics have many advantages, their poor fracture resistance and damage tolerance limit their application. In order to improve the toughness of ultra-high temperature ceramics, introducing short carbon fibers into the ultra-high temperature ceramic matrix is ​​an effective toughening method to obtain ultra-high temperature ceramic matrix composites. Ultra-high temperature ceramic matrix composites are a type of composite material with ceramic phases such as carbides or borides of transition metals such as Zr, Hf and Ta as the matrix, and particles and fibers as the toughening phase. They can usually remain non-ablated for a long time in an oxidizing environment above 2000°C, and are the most promising ultra-high temperature thermal protection materials.

[0004] However, how to evenly disperse the short carbon fibers in the matrix is ​​a difficult problem to solve. At present, the commonly used method for dispersing short carbon fibers at home and abroad is to add the short carbon fibers to the ceramic matrix powder for ball milling dispersion. Ball milling is a grinding method that uses balls as a medium to crush materials through impact, extrusion, friction, etc. However, during the ball milling mixing process, although the short carbon fibers can be evenly mixed with the ceramic matrix powder, the short carbon fibers are bound to break and be damaged due to the mutual collision of the grinding balls, which seriously affects the toughening effect of the short carbon fibers.

[0005] In addition, the current common method for preparing short carbon fiber toughened ceramic matrix composites is to mix the short carbon fibers and ceramic powders evenly by ball milling and then dry them and then hot press sinter them. After drying, the fine particles of ceramic powder will agglomerate, hindering sintering densification. Moreover, the high temperature required for hot pressing sintering will also cause erosion damage to the fibers. In addition, the raw materials usually contain some oxides, and the presence of oxides will cause grain growth, which will also hinder densification.

[0006] Therefore, the preparation of short carbon fiber toughened ultra-high temperature ceramic-based composite materials involves the problems of dispersion, damage, sintering densification difficulties of short carbon fibers, and high hot pressing sintering temperature. Chinese patent CN105906360A discloses a colloid-dispersed short carbon fiber toughened zirconium diboride-based composite material and its preparation method, which utilizes phenolic resin and polyethyleneimine to undergo cross-linking reaction to evenly disperse the short carbon fibers in the colloid, thus overcoming the fiber wear problem caused by traditional ball milling mixing; the patent adopts a colloid dispersion process, and the scheme and concept are different from the short fiber dispersion method of the present invention and the method of preparing by reactive hot pressing sintering.

[0007] Chinese patent CN105693261A discloses a ZrB2-SiC-Cf ultra-high temperature ceramic composite material and its preparation method, which adds raw material powder and carbon fiber into anhydrous ethanol for ultrasonic cleaning, and then hot press sintering after ball milling and drying; the patent adopts the ball milling method, which will cause grinding damage and length reduction to the carbon fiber during the ball milling mixing process, which is not conducive to the performance of the fiber. At the same time, the scheme and conception of the patent are also different from the short fiber dispersion method of the present invention and the method of preparing by reactive hot press sintering.

[0008] Chinese patent CN107814576A discloses a method for preparing MB2-MC-BN ultra-high temperature ceramic-based composite materials by in-situ reaction, wherein MN (M=Ti, Zr, Hf or Ta) and B4C powder are mixed, and in-situ reaction hot pressing sintering is performed in a hot pressing furnace or reaction sintering is performed in a spark plasma sintering furnace; this patent does not add short fibers, which makes the final ultra-high temperature ceramic-based composite material still brittle; and the reaction sintering system of this patent and the final ternary ceramic matrix are also different from the present invention. Summary of the invention

[0009] In view of this, the technical problem to be solved by the present invention is to provide a short carbon fiber toughened ternary ceramic matrix composite material and a preparation method thereof. The preparation method provided by the present invention can prepare a short carbon fiber toughened ternary ultra-high temperature ceramic matrix composite material. The short carbon fibers in the composite material are evenly distributed and have a long length. The composite material has high flexural strength and fracture toughness and a good degree of densification.

[0010] The present invention provides a method for preparing a short carbon fiber toughened ternary ceramic matrix composite material, comprising the following steps:

[0011] S1) adding the short carbon fibers to the ceramic matrix mixed slurry by blowing gas to disperse the short carbon fibers, thereby obtaining a dispersed mixed slurry; the ceramic matrix mixed slurry comprises MeB2, MeC, B4C, Si and resin, wherein Me is a transition metal;

[0012] S2) drying the dispersed mixed slurry obtained in step S1) and then kneading it to obtain a mixed cement;

[0013] S3) The mixed cement obtained in step S2) is subjected to reaction hot pressing and sintering to obtain a short carbon fiber toughened ternary ceramic matrix composite material.

[0014] The present invention first adds short carbon fibers to a ceramic matrix mixed slurry by gas blowing for dispersion to obtain a dispersed mixed slurry. By adding short carbon fibers by gas blowing, the short carbon fibers can be evenly distributed in the ceramic matrix mixed slurry, ensuring that the short carbon fibers are evenly dispersed, while reducing the wear damage caused by ball milling the short carbon fibers and the ceramic matrix together into a ceramic matrix mixed slurry in the prior art, and can have a good length retention, giving full play to the toughening effect of the short carbon fibers. The length of the short carbon fibers of the present invention is 2 mm to 30 mm. The gas blowing of the present invention is carried out with a gas pressure of 0.5 MPa to 0.8 MPa. The dispersion time of the present invention is 10 min to 60 min. In one embodiment of the present invention, the dispersion is ultrasonic dispersion. The interface phase of the short carbon fibers in the dispersed mixed slurry of the present invention is PyC, BN or PyC-SiC, and the thickness of the interface phase is 400 nm to 1200 nm.

[0015] The ceramic matrix mixed slurry of the present invention comprises MeB2, MeC, B4C, Si and resin, wherein Me is a transition metal, and the transition metal comprises Zr, Hf, Ti or Ta. The particle sizes of MeB2, MeC, B4C and Si of the present invention are independently 0.2 μm~5 μm, and the mass purity is 98%~99.9%. The residual carbon content of the resin of the present invention is 2%~60%. In certain embodiments of the present invention, the resin is selected from one or more of phenolic resin, polyvinyl butyral or polyvinyl pyrrolidone. The amount of the resin of the present invention accounts for 1 wt%~5 wt% of the total amount of MeB2, MeC, B4C and Si, and the amount of MeB2, MeC, B4C and Si is obtained by inverse calculation of the volume fraction of each matrix in the finally obtained short carbon fiber toughened ternary ceramic matrix composite material.

[0016] The ceramic matrix mixed slurry of the present invention is obtained by wet ball milling of MeB2, MeC, B4C, Si and resin. Specifically, the ceramic matrix mixed slurry is obtained by wet ball milling with MeB2, MeC, B4C and Si as matrix raw materials, resin as a binder, and anhydrous ethanol as a medium. The rotation speed of the wet ball milling of the present invention is 200 r / min~500 r / min, the ball-to-material ratio of the wet ball milling is (5~20):1, and the time of the wet ball milling is 5 h~24 h. After ball milling, the resin can be wrapped on the matrix raw material powder. When the temperature reaches a higher temperature later, the resin will be cracked and converted into residual carbon. The residual carbon has a higher activity and can react with the oxide introduced into the raw material during production and ball milling to promote sintering.

[0017] After obtaining the dispersed mixed slurry, the present invention dries the dispersed mixed slurry and then kneads it to obtain a mixed clay. Specifically, the dispersed mixed slurry is dried to a viscosity of 600 Pa.s to 2000 Pa.s and then kneaded. In certain embodiments of the present invention, the dispersed mixed slurry is naturally dried to a viscosity of 600 Pa.s to 2000 Pa.s and then put into a mixer for stirring and kneading. In order to ensure uniform distribution of short carbon fibers, the mixing time is 5 min to 30 min. Based on the natural volatilization of the solvent, the present invention utilizes the viscosity of the resin to directly bond the ceramic matrix raw materials together, thereby avoiding agglomeration and agglomeration of the ceramic matrix mixed slurry obtained after ball milling after drying, and promoting sintering densification.

[0018] After obtaining the mixed clay, the present invention conducts reaction hot pressing sintering on the obtained mixed clay to obtain a short carbon fiber reinforced ternary ceramic matrix composite material. In certain embodiments of the present invention, the obtained mixed clay is placed in a graphite mold for reaction hot pressing sintering to obtain a short carbon fiber reinforced ternary ceramic matrix composite material. The reaction hot pressing sintering described in the present invention is carried out under vacuum or protective gas atmosphere, and the protective gas is selected from one or more of nitrogen, helium, neon or argon. The pressure of the reaction hot pressing sintering described in the present invention is 10 MPa~50 MPa; the temperature of the reaction hot pressing sintering is 1600℃~1850℃; the time of the reaction hot pressing sintering is 30 min~120 min; the heating rate of the reaction hot pressing sintering is 3℃ / min~20℃ / min.

[0019] The present invention uses the reaction hot pressing sintering without the need for a second phase sintering aid for the preparation of a short carbon fiber reinforced ternary ceramic matrix composite material. The reaction hot pressing sintering refers to a sintering method in which, in addition to utilizing the decrease in surface free energy and mechanical force to promote the sintering mass transfer, a chemical reaction energy is added as a driving force to reduce the sintering temperature to obtain a dense ceramic. This sintering method combines the characteristics of hot pressing sintering and chemical reaction, reduces the sintering difficulty through chemical reaction, and accelerates the densification process. The present invention is based on the four materials MeB2, MeC, B4C and Si in the ceramic matrix mixed slurry, so that they can react during the hot pressing sintering process. The reaction equation is 2MeC+B4C+3Si=2MeB2+3SiC. By using the reaction hot pressing sintering, a short carbon fiber reinforced ternary ceramic matrix composite material is prepared without adding a second phase sintering aid. The sintering temperature can be reduced, the material composition and structure can be adjusted as needed, and the in-situ product has good chemical compatibility.

[0020] The present invention also provides a short carbon fiber toughened ternary ceramic matrix composite material obtained by the preparation method described in any of the above technical solutions. The short carbon fiber toughened ternary ceramic matrix composite material of the present invention is a composite material having three different matrices and a toughening material, including MeB2, MeC, SiC and short carbon fiber (abbreviated as Csf), wherein the Me is the same as above and will not be repeated; the MeB2 accounts for 30 vol%~70 vol% of the short carbon fiber toughened ternary ceramic matrix composite material; the MeC accounts for 5 vol%~15 vol% of the short carbon fiber toughened ternary ceramic matrix composite material; the SiC accounts for 15 vol%~25 vol% of the short carbon fiber toughened ternary ceramic matrix composite material; the short carbon fiber accounts for 5 vol%~40 vol% of the short carbon fiber toughened ternary ceramic matrix composite material.

[0021] Part of the MeB2 and SiC in the composite material of the present invention is obtained by the mutual reaction of MeC, B4C and Si in the ceramic matrix mixed slurry. The reaction equation is as described above and will not be repeated here. Another part of the MeB2 comes from the unreacted MeB2 in the ceramic matrix mixed slurry. Another part of the SiC is obtained by the reaction of the elemental Si in the ceramic matrix mixed slurry. Except for the part participating in the reaction, the remaining part of the MeC in the composite material comes from the unreacted MeC in the ceramic matrix mixed slurry. The elemental Si and resin in the ceramic matrix mixed slurry are consumed in the reaction hot pressing sintering.

[0022] The present invention provides a short carbon fiber toughened ternary ceramic matrix composite material and a preparation method thereof. The preparation method provided by the present invention promotes uniform dispersion of short carbon fibers and inhibits damage through the dispersion of short carbon fibers by gas blowing, removes excess oxides and promotes densification through the reaction of residual carbon and oxides after ball milling and resin cracking, and prepares the material by reaction hot pressing sintering without adding a second phase sintering aid. In particular, the raw material cost of reaction hot pressing sintering is low and the sintering temperature is low. By controlling the chemical composition of the reactants and the reaction conditions, the material composition and structure can be regulated as needed, and the in-situ product has good chemical compatibility. Therefore, reaction hot pressing sintering can densify the ceramic matrix raw material at a relatively low temperature without the need for additional sintering aids, reducing the sintering temperature while avoiding the influence of the high temperature performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the Csf / ZrB2-ZrC-SiC composite material obtained in Example 1;

[0024] Figure 2 This is a SEM image of the fiber pull-out effect of the Csf / ZrB2-ZrC-SiC composite material obtained in Example 1;

[0025] Figure 3 This is the SEM image of the Csf / ZrB2-ZrC-SiC ternary ultra-high temperature ceramic matrix composite material obtained in Example 4. DETAILED DESCRIPTION

[0026] The present invention discloses a short carbon fiber reinforced ternary ceramic matrix composite material and a preparation method thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0027] The present invention will be further described below in conjunction with embodiments:

[0028] Example 1

[0029] Step 1: Using ZrB2 powder with a purity of 99% and a particle size of 2 μm, ZrC powder with a particle size of 2 μm, B4C powder with a particle size of 2 μm and Si powder with a particle size of 5 μm as raw materials, adding 5 wt% of phenolic resin as a binder (the residual carbon content of the phenolic resin is 45%), and anhydrous ethanol as a medium, wet ball milling at a speed of 300 r / min for 12 h at a ball-to-material ratio of 5:1 to prepare a mixed slurry;

[0030] Step 2: Use gas at a pressure of 0.8 MPa to blow up short carbon fibers of 10 mm in length and add them to the mixed slurry after ball milling for ultrasonic dispersion and mixing for 30 min, wherein the interface phase of the short carbon fibers is PyC, and the thickness of the interface phase is 500 nm;

[0031] Step 3: After the short carbon fibers are added and ultrasonically dispersed, the mixed slurry is naturally dried to a viscosity of 1200 Pa.s and then put into a mixer and stirred for 10 min to ensure that the short carbon fibers are evenly distributed to obtain a mixed cement;

[0032] Step 4: Place the mixed clay in a graphite mold for reaction hot pressing sintering. The reaction hot pressing sintering conditions are argon atmosphere, heating rate of 10℃ / min, sintering pressure of 30 MPa, sintering temperature of 1800℃, and sintering time of 60 min to prepare Csf / ZrB2-ZrC-SiC composite material, in which short carbon fibers account for 10 vol% of the Csf / ZrB2-ZrC-SiC composite material, and ZrB2, ZrC and SiC matrices account for 60 vol%, 10 vol% and 20 vol%, respectively.

[0033] After testing, the short fibers in the Csf / ZrB2-ZrC-SiC ternary ultra-high temperature ceramic matrix composite material prepared in this embodiment are evenly distributed and have a long retention length. Figure 1 As shown, Figure 1 This is the SEM image of the Csf / ZrB2-ZrC-SiC composite material obtained in Example 1. The flexural strength is 317.9±20.8 MPa and the fracture toughness is 6.3±0.13 MPa.m 1 / 2 , the porosity is 0.78±0.05%.

[0034] The Csf / ZrB2-ZrC-SiC ternary ultra-high temperature ceramic matrix composite material prepared in this example exhibited an obvious fiber pull-out effect during the fracture process, which fully demonstrated its toughening effect. Figure 2 As shown, Figure 2 This is the SEM image of the fiber pull-out effect of the Csf / ZrB2-ZrC-SiC composite material obtained in Example 1.

[0035] Example 2

[0036] Step 1: Using ZrB2 powder with a purity of 98.5% and a particle size of 500 nm, ZrC powder with a particle size of 500 nm, B4C powder with a particle size of 2 μm, and Si powder with a particle size of 1 μm as raw materials, adding 5 wt% of phenolic resin as a binder (the residual carbon content of the phenolic resin is 45%), and anhydrous ethanol as a medium, wet ball milling at a speed of 300 r / min for 12 h at a ball-to-material ratio of 5:1 to prepare a mixed slurry;

[0037] Step 2: Use gas at a pressure of 0.8 MPa to blow up short carbon fibers of 10 mm in length and add them to the mixed slurry after ball milling for ultrasonic dispersion and mixing for 30 min, wherein the interface phase of the short carbon fibers is PyC, and the thickness of the interface phase is 500 nm;

[0038] Step 3: After the short carbon fibers are added and ultrasonically dispersed, the mixed slurry is naturally dried to a viscosity of 1200 Pa.s and then put into a mixer and stirred for 10 min to ensure that the short carbon fibers are evenly distributed to obtain a mixed cement;

[0039] Step 4: Place the mixed clay in a graphite mold for reaction hot pressing sintering. The reaction hot pressing sintering conditions are argon atmosphere, heating rate of 10℃ / min, sintering pressure of 30 MPa, sintering temperature of 1750℃, and sintering time of 60 min to prepare Csf / ZrB2-ZrC-SiC composite material, in which short carbon fibers account for 20 vol% of the Csf / ZrB2-ZrC-SiC composite material, while ZrB2, ZrC and SiC matrices account for 50 vol%, 10 vol% and 20 vol%, respectively.

[0040] The flexural strength of the prepared Csf / ZrB2-ZrC-SiC ternary ultra-high temperature ceramic matrix composite material is 250.3±12.7 MPa, and the fracture toughness is 6.6±0.15 MPa.m 1 / 2 , the porosity is 0.95±0.04%.

[0041] Example 3

[0042] Step 1: using HfB2 powder with a purity of 99% and a particle size of 2 μm, HfC powder with a particle size of 2 μm, B4C powder with a particle size of 2 μm and Si powder with a particle size of 5 μm as raw materials, adding 5 wt% of polyvinyl butyral as a binder (the residual carbon content of the polyvinyl butyral is 10%), anhydrous ethanol as a medium, and wet ball milling at a speed of 300 r / min for 12 h to prepare a mixed slurry at a ball-to-material ratio of 5:1;

[0043] Step 2: Use gas at a pressure of 0.8 MPa to blow up short carbon fibers of 5 mm in length and add them into the mixed slurry after ball milling for ultrasonic dispersion and mixing for 30 min, wherein the interface phase of the short carbon fibers is PyC, and the thickness of the interface phase is 500 nm;

[0044] Step 3: After the short carbon fibers are added and ultrasonically dispersed, the mixed slurry is naturally dried to a viscosity of 1000 Pa.s and then put into a mixer and stirred for 10 min to ensure that the short carbon fibers are evenly distributed to obtain a mixed cement;

[0045] Step 4: Place the mixed clay in a graphite mold for reaction hot pressing sintering. The reaction hot pressing sintering conditions are argon atmosphere, heating rate of 10℃ / min, sintering pressure of 30 MPa, sintering temperature of 1800℃, and sintering time of 60 min to prepare Csf / HfB2-HfC-SiC composite material, in which short carbon fibers account for 10 vol% of the Csf / HfB2-HfC-SiC composite material, while HfB2, HfC and SiC matrices account for 60 vol%, 10 vol% and 20 vol%, respectively.

[0046] The flexural strength of the prepared Csf / ZrB2-ZrC-SiC ternary ultra-high temperature ceramic matrix composite material is 360±16.8 MPa, and the fracture toughness is 6.4±0.11 MPa.m 1 / 2 , the porosity is 0.65±0.08%.

[0047] Comparative Example 1

[0048] Step 1: Using ZrB2 powder with a purity of 99% and a particle size of 2 μm, ZrC powder with a particle size of 2 μm, B4C powder with a particle size of 2 μm and Si powder with a particle size of 5 μm as raw materials, adding 5 wt% of phenolic resin as a binder (the residual carbon content of the phenolic resin is 45%), and anhydrous ethanol as a medium, wet ball milling at a speed of 300 r / min for 12 h at a ball-to-material ratio of 5:1 to prepare a mixed slurry;

[0049] Step 2: Add short carbon fibers with a length of 10 mm directly into the ball-milled mixed slurry and perform ultrasonic dispersion mixing for 30 min, wherein the interface phase of the short carbon fibers is PyC, and the thickness of the interface phase is 500 nm;

[0050] Step 3: After the short carbon fibers are added and ultrasonically dispersed, the mixed slurry is naturally dried to a viscosity of 1200 Pa.s and then put into a mixer and stirred for 10 min to ensure that the short carbon fibers are evenly distributed to obtain a mixed cement;

[0051] Step 4: Place the mixed clay in a graphite mold for reaction hot pressing sintering. The reaction hot pressing sintering conditions are argon atmosphere, heating rate of 10℃ / min, sintering pressure of 30 MPa, sintering temperature of 1800℃, and sintering time of 60 min to prepare Csf / ZrB2-ZrC-SiC composite material, in which short carbon fibers account for 10 vol% of the Csf / ZrB2-ZrC-SiC composite material, and ZrB2, ZrC and SiC matrices account for 60 vol%, 10 vol% and 20 vol%, respectively.

[0052] The results show that the short fibers in the prepared Csf / ZrB2-ZrC-SiC ternary ultra-high temperature ceramic matrix composite material have obvious agglomeration phenomenon, such as Figure 3 As shown, Figure 3 This is a SEM image of the Csf / ZrB2-ZrC-SiC ternary ultra-high temperature ceramic matrix composite material obtained in Comparative Example 1. The flexural strength of the Csf / ZrB2-ZrC-SiC ternary ultra-high temperature ceramic matrix composite material obtained in Comparative Example 1 is 220.5±16.4 MPa, and the fracture toughness is 5.2±0.19 MPa.m 1 / 2 , the porosity is 1.5±0.18%.

[0053] Comparative Example 2

[0054] Step 1: Using ZrB2 powder with a purity of 99% and a particle size of 2 μm, ZrC powder with a particle size of 2 μm and SiC powder with a particle size of 500 nm as raw materials, adding phenolic resin with a residual carbon content of 5 wt% as a binder (the phenolic resin has a residual carbon content of 45%), and anhydrous ethanol as a medium, wet ball milling at a speed of 300 r / min for 12 h at a ball-to-material ratio of 5:1 to prepare a mixed slurry;

[0055] Step 2: Add short carbon fibers with a length of 10 mm directly into the ball-milled mixed slurry and perform ultrasonic dispersion mixing for 30 min, wherein the interface phase of the short carbon fibers is PyC, and the thickness of the interface phase is 500 nm;

[0056] Step 3: After the short carbon fibers are added and ultrasonically dispersed, the mixed slurry is naturally dried to a viscosity of 1200 Pa.s and then put into a mixer and stirred for 10 min to ensure that the short carbon fibers are evenly distributed to obtain a mixed cement;

[0057] Step 4: Place the mixed clay in a graphite mold for hot pressing and sintering. The hot pressing and sintering conditions are argon atmosphere, a heating rate of 10 ℃ / min, a sintering pressure of 30 MPa, a sintering temperature of 1800 ℃, and a sintering time of 60 min to prepare a Csf / ZrB2-ZrC-SiC composite material, in which short carbon fibers account for 10 vol% of the Csf / ZrB2-ZrC-SiC composite material, and ZrB2, ZrC and SiC matrices account for 60 vol%, 10 vol% and 20 vol%, respectively.

[0058] The results show that the short fibers in the prepared Csf / ZrB2-ZrC-SiC ternary ultra-high temperature ceramic matrix composite are evenly distributed and have long retention lengths. The flexural strength is 160±23.5 MPa and the fracture toughness is 3.12±0.14 MPa.m 1 / 2 , the porosity is 10±0.34%.

[0059] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a short carbon fiber toughened ternary ceramic matrix composite material, characterized in that: The following steps are involved: S1) adding the short carbon fibers to the ceramic matrix mixed slurry by blowing gas to disperse the short carbon fibers, thereby obtaining a dispersed mixed slurry; the ceramic matrix mixed slurry comprises MeB2, MeC, B4C, Si and resin, wherein Me is a transition metal; S2) drying the dispersed mixed slurry obtained in step S1) and then kneading it to obtain a mixed cement; S3) The mixed cement obtained in step S2) is subjected to reaction hot pressing and sintering to obtain a short carbon fiber toughened ternary ceramic matrix composite material.

2. The preparation method according to claim 1, characterized in that: In step S1), the gas blowing is performed using a gas with a pressure of 0.5 MPa to 0.8 MPa.

3. The preparation method according to claim 1, characterized in that: In step S1), the interfacial phase of the short carbon fibers in the dispersed mixed slurry is PyC, BN or PyC-SiC, and the thickness of the interfacial phase is 400 nm to 1200 nm.

4. The preparation method according to claim 1, characterized in that: In step S1), the residual carbon content of the resin is 2% to 60%.

5. The preparation method according to claim 1, characterized in that: In step S1), the amount of the resin accounts for 1 wt% to 5 wt% of the total amount of MeB2, MeC, B4C and Si.

6. The preparation method according to claim 1, characterized in that: In step S1), the length of the short carbon fiber is 2 mm to 30 mm; The particle sizes of MeB2, MeC, B4C and Si are independently 0.2 μm to 5 μm; The resin is selected from one or more of phenolic resin, polyvinyl butyral or polyvinyl pyrrolidone.

7. The preparation method according to claim 1, characterized in that: In step S1), the ceramic matrix mixed slurry is obtained by wet ball milling of MeB2, MeC, B4C, Si and resin; The rotation speed of the wet ball mill is 200 r / min~500 r / min, the ball-to-material ratio of the wet ball mill is (5~20):1, and the time of the wet ball mill is 5 h~24 h.

8. The preparation method according to claim 1, characterized in that: In step S3), the pressure of the reaction hot pressing sintering is 10 MPa to 50 MPa; The temperature of the reaction hot pressing sintering is 1600°C to 1850°C; The reaction hot pressing sintering time is 30 min to 120 min.

9. The short carbon fiber toughened ternary ceramic matrix composite material obtained by the preparation method according to any one of claims 1 to 8.

10. The short carbon fiber toughened ternary ceramic matrix composite material according to claim 9, characterized in that: It includes MeB2, MeC, SiC and short carbon fibers; The MeB2 accounts for 30 vol% to 70 vol% of the short carbon fiber toughened ternary ceramic matrix composite material; The MeC accounts for 5 vol% to 15 vol% of the short carbon fiber toughened ternary ceramic matrix composite material; The SiC accounts for 15 vol% to 25 vol% of the short carbon fiber toughened ternary ceramic matrix composite material; The short carbon fibers account for 5 vol% to 40 vol% of the short carbon fiber toughened ternary ceramic matrix composite material.

Citation Information

Patent Citations

  • ZrB2-SiC-Cf ultra-high temperature ceramic composite material and preparation method thereof

    CN105693261A

  • Zirconium diboride-based composite material toughened by colloid-dispersed chopped carbon fibers and preparation method thereof

    CN105906360A

  • Method for preparing MB2-MC-BN ultrahigh temperature ceramic matrix composite by in-situ reaction

    CN107814576A

  • Short-fiber-reinforced pultrusion composite material solar energy assembly frame and preparation method thereof

    CN104761880A

  • Preparation method for short fiber reinforced silicon carbide ceramic matrix composite

    CN106977222A